Penyiapan Sumber Daya Perempuan dalam Politik Indonesia di Akar Rumput - Amanda Setiorini; M. Zein Saleh (Jurnal Deliberatif, 2023)
The representation of women in legislative bodies is constrained by cadres at the grassroots. This paper aims to analyze the preparation of women's resources in politics related to individual interests and the interests of political parties. The data obtained from the survey shows that women feel uninterested because they are not familiar with the world of politics. They also feel they have the ability to become members of the legislature, despite their relatively high tendency to get approval from their families/spouses. The discussion in this article refers to efforts to change so that the preparation of women's resources in politics can be done with a different approach.